(untitled) (Journal SCIENCEVOLUTION, 2026)
Artificial intelligence has been established as a technology that transforms business strategies by optimizing sales processes through automation, predictive models, and advanced personalization. Although multiple studies exist, there is still insufficient evidence to draw firm conclusions about its overall impact on organizations. Therefore, this systematic review aimed to examine the incorporation of artificial intelligence into business strategies for sales process automation, identifying its trends, benefits, and challenges in order to provide a solid foundation for future research. The search conducted in Scopus, Web of Science (WoS), ScienceDirect, SpringerLink, IEEE Xplore, and Google Scholar yielded a total of 120 articles; after the screening process, 10 studies were selected. The methodological quality of the included articles was assessed using an adaptation of the NOS scale. The findings indicated that AI increases predictive accuracy, enhances customer management, and enables hyper-personalization and operational efficiency. They also revealed challenges such as data quality issues, cultural resistance, talent shortages, and ethical risks. It was concluded that AI is an effective tool for optimizing commercial processes; however, further research is needed to strengthen the evidence regarding its effectiveness and sustainability.